Seroepidemiology and genotyping of hepatitis E virus in Singapore reveal rise in number of cases and similarity of human strains to those detected in pig livers. (11th July 2019) - Wong, Chui Ching; Thean, Su Ming; Ng, Youming; Kang, Joanne Su Lin; Ng, Tong Yong; Chau, Man Ling; Koh, Tse Hsien; Chan, Kwai Peng
Abstract: Hepatitis E virus (HEV) causes 20 million infections worldwide yearly, of which only about 3.3 million are symptomatic. In developed Asian countries, HEV strains detected in human sera and in food sources were genetically similar, suggesting that indigenous HEV infections may be largely food‐borne. To assess the burden of hepatitis E in Singapore, we performed a seroepidemiologic study of the infection. Additionally, we carried out HEV genotyping on archived, residual HEV IgM‐positive serum samples collected between 2014 and 2016 ( n  = 449), and on pig liver samples ( n  = 36) purchased from wet markets and supermarkets. Our study shows a rise in hepatitis E incidence (IgM) from 1.7 to 4.1 cases per 100, 000 resident population from 2012 to 2016 and an increase in hepatitis E IgG positivity rate among residents from 14% in 2007 to 35% in 2016. Other findings also suggest the epidemiology of hepatitis E in Singapore has shifted, from it being mainly a disease imported from the Indian subcontinent, to one that is now increasingly prevalent in our resident population. Genotypes obtained from 143 human samples identified the majority to be genotype 3 ( n  = 121), 21 to be genotype 1 and one to be genotype 4. Further phylogenetic analyses suggest genotype 3a to be the cause of indigenous infections in residents, which showed genetic similarity to the genotype 3a strains detected in pig livers. This link between the strains in the majority of human samples and those in pig livers consumed by the public suggests a possible food‐borne route of HEV infection in Singapore.